2011
DOI: 10.1186/1756-9966-30-36
|View full text |Cite
|
Sign up to set email alerts
|

Factors that contribute to long-term survival in patients with leukemia not in remission at allogeneic hematopoietic cell transplantation

Abstract: BackgroundThere has been insufficient examination of the factors affecting long-term survival of more than 5 years in patients with leukemia that is not in remission at transplantation.MethodWe retrospectively analyzed leukemia not in remission at allogeneic hematopoietic cell transplantation (allo-HCT) performed at our institution between January 1999 and July 2009. Forty-two patients with a median age of 39 years received intensified conditioning (n = 9), standard (n = 12) or reduced-intensity conditioning (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Furthermore, the 1-year estimated OS after transplantation was higher in patients with CR/CRi than in patients with PR/NR, and the relapse rate was lower in the CR/CRi group than in the PR/NR group. These results suggest that a lower leukemia cell burden prior to transplantation enabled a reduced risk to relapse post transplantation (40). Collectively, the achievement of CR/CRi with BHA provided a time window to conduct allogeneic transplantation, thereby yielding a better survival in R/R AML, particularly in patients with FLT3-mutated AML.…”
Section: B Amentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, the 1-year estimated OS after transplantation was higher in patients with CR/CRi than in patients with PR/NR, and the relapse rate was lower in the CR/CRi group than in the PR/NR group. These results suggest that a lower leukemia cell burden prior to transplantation enabled a reduced risk to relapse post transplantation (40). Collectively, the achievement of CR/CRi with BHA provided a time window to conduct allogeneic transplantation, thereby yielding a better survival in R/R AML, particularly in patients with FLT3-mutated AML.…”
Section: B Amentioning
confidence: 83%
“…It is well known that the elimination of minimal residual disease of leukemic cells prior to allogeneic HSCT plays a critical role in preventing AML relapse after transplantation. For instance, it has been reported that tumor burden prior to allogeneic transplantation is strongly associated with a high risk of relapse and negatively impacts long-term outcomes following allogeneic HSCT (40,41). Moreover, Duval et al (7) found that patients with CR before transplantation had higher OS rates.…”
Section: B Amentioning
confidence: 99%
“…Some patients with refractory disease may be taken directly to transplant with active disease, but cure rates are low in these cases [33]. In one study, leukemia free survival at 5 years was 17% in patients taken to transplant with leukemia that was not in remission [34].…”
Section: 4mentioning
confidence: 98%
“…Biologically, significant advances in the identification and molecular characterization of genetic alterations that have an important role in the biology and evolution of B-ALL have been described [ 3 ]. In adult patients, B-ALL has a poor clinical outcome and low survival rates with an estimated rate of complete remission (CR) of 75% and disease-free survival (DFS) lower than 30% [ 4 7 ]. Currently, the criteria used to stratify patients into risk groups at diagnosis is based on a range of variables that include age at diagnosis, white blood cell count (WBCC), and cytogenetic and chromosomal alterations [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%